1992
DOI: 10.1016/0014-5793(92)81074-v
|View full text |Cite
|
Sign up to set email alerts
|

Lipid interaction of Tetanus neurotoxin A calorimetric and fluorescence spectroscopy study

Abstract: The imcruslion of Taanus toxin with phorpholipid vcsicla conulining gamylioridcr (CiDIa. GDlb or CTlb) or phorphalidic ucid hrs been inwzrtigntcd PI nculrnl or acidic pH, Chsrngc in the thcrmolropic proper& of the vclctcs eeurrcd only uficr addilion of ihc toxin at acidic pM, and Icd LO rurbcc bindins or mcmbnnc inrcrrion ofthc prolcin, dcpcndcnt on the phyriul LMC oftbc mcmbranc, Mosl rcmlrrkably, toxin addition YI ticidic pCI IO dipulmitoyl~pl~orpb~iidylchclinc vcrirlcr containinpGT1 b yolnylioridc, caurd fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…As the Tet C fragment is the membrane-binding domain, it is likely that its interactions with G T1b would be sensitive to changes in pH. This result is in contrast to work by others who have examined the formation of pores in lipid membranes by the full-length tetanus toxin at low pH (57)(58)(59)(60).…”
Section: Figurementioning
confidence: 79%
“…As the Tet C fragment is the membrane-binding domain, it is likely that its interactions with G T1b would be sensitive to changes in pH. This result is in contrast to work by others who have examined the formation of pores in lipid membranes by the full-length tetanus toxin at low pH (57)(58)(59)(60).…”
Section: Figurementioning
confidence: 79%
“…Ean der Goot, Gonzalez-Manas, Lakey, and Pattus (1991) observed that, depending on circumstances, the pH in the vicinity of the membrane might be 1-3 units lower than in the bulk solution. A decrease in pH has been linked to structural changes in many proteins, such as the Bt toxin Cry1C (Butko, Cournoyer, Pusztai-Carey, & Surewicz, 1994), P. aeruginosa exotoxin A (Menestrina, Pederzolli, Forti, & Gambale, 1991), tetanus toxin (Calappi, Masserini, Schiavo, Montecucco, & Tettamanti, 1992), and tumor necrosis factor a (Kagan, Baldwin, Munoz, & Wisnieski, 1992). All of these proteins increase their affinity to the membrane at acidic pH (Manceva, Pusztai-Carey, & Butko, 2004).…”
Section: Antimicrobial Activity and Hemolytic Activitymentioning
confidence: 97%
“…There is experimental evidence that glycolipid‐enriched domains are a target for certain diseases, some of them of particular interest for the nervous system: Alzheimer’s disease, prion diseases, and neurolipidoses, which will be discussed. However, it is worth reminding that also the neuron‐specific toxin of Clostridium tetani induces, in vitro, formation of ganglioside domains, which were postulated to be involved in the mechanism of toxin internalization (Calappi et al, 1992).…”
Section: Pathological Implicationsmentioning
confidence: 99%